Code name Verity [large type] - Wein, Elizabeth (Thorndike Press, a part of Gale, Cengage Learning, 2013)
In 1943, a British fighter plane crashes in Nazi-occupied France and the survivor tells a tale of friendship, war, espionage, and great courage as she relates what she must to survive while keeping secret all that she can.